Study on the Effect of Bilateral Mandible Distraction Osteogenesis About the Nutrition Status of Infants With Pierre-Robin Sequence - Jiayu, Liu; Jing, Sun; Yiyang, Chen; Fan, Li (Frontiers in Pediatrics, 2021)
[Objective] By comparing and studying the changes of food intake, weight, body length, BMI, blood albumin level and other indicators of infants with Pierre-Robin Sequence before and after Bilateral Mandible Distraction Osteogenesis operation, to explore the effect of distraction osteogenesis on PRS patients about the improvement of nutrition status. [Methods] The children with PRS who admitted to the Oral and Maxillofacial Surgery Department of Guangzhou Women and Children's Medical Center from July 2015 to December 2020 were selected. All patients accepted bilateral mandible distraction osteogenesis surgery, and the pre- and post-operative indicators were recorded, such as food intake, weight, length, blood albumin level and others. BMI was calculated based on the indicators mentioned above, and comparative statistical analysis was performed. [Results] 1. All patients were fed with whole milk before the first surgery, and the average calorie per kg was 91.8kcal/kg, significantly lower than the standard (100-150kcal/kg), suggesting the overall nutritional intake of PRS patients is low; 2. t tests for independent samples were used to analyze the preoperative and postoperative indicators. The WFA percentile increased from 14.16±2.17% to 15.01±1.85% (P=0.0048), WFA z score increased from -2.40±0.18 to -1.90±0.14 after the surgery (P=0.0010 ), LFA percentile increased from 20.04±3.48% to 33.67±4.29% (P=0.0098), LFA z score increased from -2.09±0.19 to -1.42±0.23 (P=0.0009), BMI z score increased from -1.95±0.22 to -1.39±0.16 (P=0.0408), ALB raised from 37.06±0.51g/L to 42.85±0.30g/L (P＜0.001),which indicating that the physique of patients improved after the distraction osteogenesis surgery, mainly was reflected by the lifting of weight and length growth curves; the body shape also improved, indicating that the patients’ nutrition status after the surgery is also improved. [Conclusion] Bilateral mandible distraction osteogenesis surgery has a positive effect on the nutrition status of children with Pierre Robin Sequence. This effect is mainly reflected by the improvements of the body physical indicators after surgery.